Drilling and Blasting with Large Equipment: Sustainable Mining Near Communities - Mattos J. L. C (International Society of Explosives Engineers, 2026)
Drilling and blasting with explosives in mining operations near communities require careful planning to mitigate socio-environmental impacts. Ground vibration, noise emission, flyrock, and dust dispersion are factors that may trigger conflicts with local populations. However, large-scale operations demand high productivity and intense material handling, making it essential to balance operational performance with impact control. The adoption of best practices, combined with advanced monitoring and mitigation technologies, enables sustainable mining even in proximity to inhabited areas. This study proposes the use of double and triple-deck blasting techniques with large-diameter boreholes (12 ¼” – 311 mm), addressing the sizing of charges and decks, as well as measures aimed at reducing noise perceived by nearby communities. The approach seeks to maintain the use of large drilling rigs already present in the operation, avoiding costs related to premature equipment replacement or expensive alternatives, while minimizing environmental and social impacts and promoting a more balanced and responsible mining model.